Karang Taruna Enterprise Development DKI Jakarta - Meiryani Meiryani; Jajat Sudrajat; Isana Wikrama (Bina Nusantara University, 2020)
The purpose of this activity is to motivate and inspire the DKI Jakarta Youth Organization through the theme of Entrepreneurship Development for the Jakarta Youth Organization. Participants in this activity were Binus Syahdan Campus Cleaning Service officers and Anggrek representing West Jakarta Youth Organization. This activity shows the enthusiasm of the participants because of their entrepreneurial development potential, because there are already several people who already have products, but are not optimal in their packaging and marketing, currently by optimizing social media networking alone. The results of this activity have several implications, including the following; First, the implications for planning and developing the training curriculum for MSMEs, Candidates for MSMEs and Communities and teaching materials for the EN001 Entrepreneurship course, with the collaboration method of lecturers, students and MSMEs in carrying out community service activities, by optimizing the implementation of the Entrepreneurship Student Activity Program (PKM-K) through Higher Education Grants in the Indonesian Student Business Competition Program (KBMI). Second, the implications for the education and training of lecturers by using an example method of direct practical application. Third, to inspire to increase cooperation with lecturers from different study programs, so that the output can make further proposals for funding other than the Binus grant. Fourth, the implications of choosing the right training / workshop method for participants and the community as well as increasing the synergy in the implementation of the Tridharma of Higher Education.